Literature Review of Artificial Intelligence in Augmented Reality for Adaptive Learning - Bintang Eka Putera; Julia Fajaryanti (Institute of Computer Science (IOCS), 2026)
Although Artificial Intelligence (AI) and Augmented Reality (AR) have attracted increasing attention in education, their combined role in adaptive learning remains fragmented across existing studies. This review examines how AI is applied in AR-based learning environments, the benefits of AI–AR integration, and the associated challenges. The reviewed studies show that AI supports personalization through intelligent tutoring systems, adaptive feedback, learning analytics, and generative AI, while AR enhances visualization, engagement, and immersive learning experiences. This review synthesizes the complementary roles of AI and AR, highlights current research trends and gaps, and provides insights for educators and researchers developing adaptive learning environments.